Effects of simultaneous versus post exposure epigallocatechin-3-gallate treatment on aluminum induced neurotoxicity in rat hippocampus: A multi-approach study - Palabiyik-Yucelik, Saziye Sezin; Zeybek, Naciye Dilara; Cinar, Irfan; Akpinar, Erol; Zirh, Elham Bahador; Sipahi, Hande; Halici, Zekai (Elsevier BV, 2023)
Chronic aluminium(Al) exposure can affect the antioxidant and glutaminergic systems through N-methyl-D-aspartate receptors (NMDAR). This study was aimed to investigate the neurotoxic effect of Al through different mechanisms in rat hippocampus and to evaluate the protective role of epigallocatechin gallate (EGCG), a well-known antioxidant, with simultaneous administration of Al,as well as post-treatment after Al exposure.For this purpose, aluminum chloride(AlCl3) was administered simultaneously with two different EGCG doses for 8 weeks as the first part of the study.In the second part of the study, after 4 weeks of AlCl3 pre-administration, two different EGCG doses were also administered during four additional weeks as post-treatment.Al administration led to oxidative stress and increased acetylcholinesterase levels.NMDAR subunit mRNA expressions were down-regulated by Al, which was apparent in NMDAR1/2B subunits.Simultaneous EGCG treatment has shown a better neuroprotective effect in terms of these mechanisms and represents novel approach for the prevention of neurodegenerative diseases likely to be induced by Al.
Keywords: Assay; Expression; Diseases; Stress; Hippocampus; Antioxidants; Catechin; Acetylcholinesterase Activity; Neurotoxicity; Acid; Animals; Rats, Wistar; Inhibition; Epigallocatechin gallate; Rats; NMDAR; Nitric-Oxide; Oxidative Stress; Neuroprotective Agents; Acetylcholinesterase; Neurotoxicity Syndromes; Aluminum; 3. Good health